Analisis Maslahah Mursalah terhadap Jual Beli Limbah Dikaitkan dengan Green Ekonomi - Ade Halen Pebrio; Muhammad Yunus (UPT Publikasi Ilmiah Unisba, 2023)
In Kagok Village, Majalengka, there's a practice of buying and selling chicken waste. Shafi'i and Hanabillah scientists consider it forbidden, while Hanafiah and Zahiri argue it's permissible due to its benefits. So the purpose of this study is to analyze the practice of buying and selling chicken manure waste in Kagok Village, Majalengka Regency, analyze the concept of maslahah mursalah on the practice of buying and selling chicken manure waste to the village community, and analyze the practice of buying and selling chicken manure waste on the green economy. The frame of mind made by the author is first buying and selling sewage waste, mursalah maslahah and green economy. The research method used is qualitative. The research findings are the practice of buying and selling chicken manure waste in Kagok Village. The result of this study is that the sale and purchase of chicken manure waste in Kagok Village is allowed on the grounds that there is a beneficial value. This benefit is created between sellers and buyers of livestock manure waste where mutual benefits as fertilization needs in the form of organic fertilizer for farmers and economic value for farmers. The harmony between the sale and purchase of chicken manure waste with the green economy is in the form of labor from local residents and waste reduction by trading it to farmers and even given voluntarily to farmers. Di Desa Kagok, Majalengka, terdapat praktik jual beli sampah ayam. Ilmuwan Shafi'i dan Hanabillah menganggapnya haram, sementara Hanafiah dan Zahiri berpendapat halal karena manfaatnya. Oleh karena itu tujuan penelitian ini adalah untuk menganalisis praktek pembelian dan penjualan limbah ayam di Desa Kagok, menganalisa konsep maslahah mursalah pada praktek membeli dan menjual limbah Ayam ke masyarakat desa, dan menganalisakan praktek belanja dan penjual limbah daging ayam pada ekonomi hijau. Kerangka pikir yang dibuat oleh penulis adalah pertama membeli dan menjual limbah, mursalah maslahah dan ekonomi hijau. Metode penelitian yang digunakan adalah kualitatif. Temuan penelitian adalah praktek pembelian dan penjualan limbah ayam di Desa Kagok. Hasil dari penelitian ini adalah bahwa penjualan dan pembelian limbah ayam di Desa Kagok diizinkan dengan alasan bahwa ada nilai manfaat. Keuntungan ini diciptakan antara penjual dan pembeli limbah peternakan di mana saling menguntungkan seperti kebutuhan pupuk dalam bentuk pupuk organik bagi petani dan nilai ekonomi bagi para petani. Harmonisasi antara penjualan dan pembelian limbah ayam dengan ekonomi hijau adalah dalam bentuk tenaga kerja dari penduduk setempat dan pengurangan limbah dengan menjualnya kepada petani dan bahkan diberikan secara sukarela ke petani.